Personality and project management success - Anna Ellen Douglas 1975- (2020)
Significant research has been devoted to the topic of leadership and project success, and the positive relationship between the two. The influence of personality traits on project leadership competence has been researched to a lesser extent. It is a very relevant topic considering the importance of emotional/social intelligence and communication skills in today’s diverse and complex project environments. It is not only a useful undertaking for project leaders to develop the essential traits and behaviours for success, but a fundamental element in leading successful projects. This paper presents a quantitative study to investigate the possible link between project manager personality traits and their level of success in project management. A self-reporting questionnaire was used to measure the self-perceived success of a sample of project managers in Iceland. The questionnaire also included the NEO FFI-R personality test. The results indicate that Conscientiousness, Extraversion, and Openness to experience to a lesser extent, seem to correlate positively with project manager success, and Neuroticism appears to correlate negatively with project manager success. Agreeableness did not show a significant correlation with successful project management. Furthermore, the results indicate certain commonalities among project managers, such as higher Openness, Extraversion, and Conscientiousness when compared to the general population. The research findings may support a better understanding of the traits that are important for project managers and organisations to develop, promote and recruit for, with the aim of positively impacting project success.